Reaksi Pasar Terhadap Pengumuman Pembelian Kembali Saham (Buy Back) Pada Perusahaan yang Terdaftar di BEI tahun 2013-2014 - Komaeroh, Siti; Salim, Ubud (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this study is to determine the market reaction to the share repurchase (buy back) announcement that are indicated by the change of abnormal return and share trading volume activity significantly. The model of this research is event study which conducted by using 18 companies as samples, which perform buy backing at period 2013-2014 in the Indonesia Stock Exchange (IDX). The sampling technique of this study is purposive sampling method. Based On the result of hypothesis testing, this study found that investors perform significant reaction to the buy back announcement as which appeared by the average trading volume activity of all-day observation period. However, this study did not find any significant average abnormal return (AAR) among the share repurchase announcement (buy back), and also did not find differences on average of abnormal return and average of trading volume activity before and after the buy back announcement. This occurs due to investors tend to act